The use of starch microspheres and nanoparticles in pharmaceutical applications - Fureby, Anna Millqvist; Gidlöf, Zandra; Wahlgren, Marie ; 0000-0002-1705-3964 (Starch in Food : Structure, Function, and Applications, 2024)
Starch is generally regarded as safe for human consumption and has therefore attracted interest for several applications as medicinal products. This chapter focuses specifically on starch microspheres as carriers for drug delivery and as a medical device for, for example, vascular occlusion. Several methods for the preparation of starch microspheres by chemical or physical cross-linking are presented. The properties of the starch microspheres are affected by the production method, which also influences what applications they are suited for, and how active substances can be included in the microspheres. The current and potential applications of starch microspheres in drug delivery, vascular occlusion, and advanced wound care are reviewed.
Publisher Copyright: © 2024 Elsevier Ltd. All rights reserved.
Keywords: Advanced wound care; Antisolvent precipitation; Aqueous two-phase systems; Chemical cross-linking; Drug delivery; Physical cross-linking; Spray drying; Starch microspheres; Vascular occlusion